The Implementation of Quranic Sciences Curriculum at an Islamic Boarding School in Bondowoso, East Java - Ahmad Amiruddin; Moch. Imam Machfudi; Muhammad Haidlor (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research examined the implementation of Quranic sciences Curriculum in Nurul Burhan Islamic Boarding School in Badean Bondowoso, East Java. This research employed qualitative research case study design which intended : (1) to describe the material or content standard of the implementation of Quranic Sciences curriculum (2) to describe the processing standard of the implementation of Quranic Sciences curriculum, and (3) to describe the evaluation standard of the implementation of Quranic Sciences curriculum. In presenting the data, this research explored specific phenomena (cases) in a given time and activity (program, event, process, institution or social group) and gather detailed and in-depth information using various data collection procedures over a certain period. The researchers used the third type of case study that was intrinsic case study. Intrinsic case study is focused on the case itself. The result and data analysis revealed that the implementation of the Quranic sciences curriculum included: First, the materials used in learning are connected with other materials, essentially all existing materials have been included in the Quranic sciences. Second, the learning process showed that Nurul Burhan has implemented the Islamic principle as stated in Islamic classic book (kitab kuning), especially in terms of students’ interaction with teachers and the learning methods used. Third, Nurul Burhan Islamic Boarding School uses three types of evaluation to keep the sustainability of the learning process in accordance with Quranic science curriculum.